PENGARUH KOMPETENSI PROFESIONAL, MOTIVASI, DAN KONSEP DIRI TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA SEKECAMATAN CINA KABUPATEN BONE - Tansini Tansini; Andi Jam'an; Amelia Rezky Amin (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
This study aims to see and analyze professional competence, motivation, and self-concept on the performance of state junior high school teachers in the Chinese District of Bone Regency and to analyze and analyze the effects of competence, motivation, and self-concept on the performance of junior high school teachers. country of the District of China, Bone Regency. The analytical method used in this research is quantitative descriptive method with multiple regression testing, by performing validation and reliability tests of the question items for each variable as well as testing assumptions. The trial of 105 question items contained 24 invalid items so that the remaining 81 items were valid.The results of this study indicate that the coefficient of the influence of professional competence on teacher performance is 0.417 which is in the medium category with a value of p = 0.039 0.05. This shows that professional competence has a significant effect on teacher performance of 0.905 which is in the very high category with p = 0.000 0.05. This shows that motivation has a significant effect on teacher performance. And the value of F = 11.147 with a value of p = 0.00, this is the basis for decision making that the variables of professional competence, motivation, and self-concept together have an effect on teacher performance. This means that the better professional competence, motivation, and concepts owned by a teacher, the performance of public junior high school teachers in the Chinese District of Bone Regency will increase. Keywords: professional competence, motivation, self-concept and performance